The Effect of Lecturer Performance on Student Satisfaction of Information Academic and Medicom Computers - Bena Br Ginting (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to analyze the effect of lecturer performance on student satisfaction at the Medicom Informatics and Computer Academy. In this study, there were two variables, including one independent variable, namely Lecturer Performance (X) and one dependent variable, namely Student Satisfaction (Y). This research was conducted on Medicom students, the number of samples in this study was 40 people. This type of quantitative research. And in this study intends to test the hypothesis in the hope of confirming or strengthening the assumptions that have been formulated which in turn can support the theory. Based on these assumptions, the type of research used includes Explanatory Research through associative research. Data collection techniques through literature study, questionnaires. The data analysis technique used hypothesis testing and multiple regression analysis. The calculation uses SPSS for windows version 17. The results of the hypothesis test show that lecturer performance has a positive and significant effect on student satisfaction with the tcount value of the Lecturer Performance variable being 2.755 while the ttable is 1.685. It was concluded that the lecturer's performance had a positive and significant effect on student satisfaction at the Medicom Informatics and Computer Academy.